Ewa Ciszewska and Mikolaj Góralik (ed.): Polsko-czeskie i polsko-słowackie kontakty filmowe - Miroslav Zelinský (Apparatus. Film, Media and Digital Cultures of Central and Eastern Europe, 2019)
Miroslav Zelinský`s review of the book